Adults with intellectual disability and Attention Deficit Hyperactivity Disorder: Clinical characteristics and medication profiles. (22nd March 2019) - Al‐Khudairi, Rashed; Perera, Bhathika; Solomou, Solomis; Courtenay, Ken
Accessible summary: Attention deficit hyperactivity disorder (ADHD) is often missed/underdiagnosed in people with intellectual disability compared to people without intellectual disability. The presence of intellectual disability, autism and challenging behaviour should raise the suspicion of ADHD as comorbid neurodevelopmental disorder. Treatment of ADHD in people with intellectual disability may reduce the need for antipsychotic medications. Abstract: The diagnosis of ADHD is often missed or misdiagnosed in people with intellectual disability. Despite a significant growth in literature on the diagnosis and treatment of ADHD in people without intellectual disability, there have been few studies on ADHD in people with intellectual disability. In this paper, we describe a group of adults with intellectual disability and ADHD disorder open to a specialist community intellectual disability service. We examined the frequency and dose of antipsychotic use and considered whether ADHD disorder medication is associated with a reduced use of psychotropic medication. The study found a high incidence of autism in people with intellectual disability and ADHD. Men with intellectual disability were given the diagnosis of ADHD more often compared to women with intellectual disability. Only 64% of people with ADHD and intellectual disability taking ADHD medication were on antipsychotic medications compared to 93% of people with ADHD and intellectual disability without ADHD medications. This generates several hypotheses such as whether antipsychotic medications are prescribed to control ADHD symptoms, whether use of ADHD medications can reduce the use of antipsychotic medications and/or whether antipsychotics are used to treat underlying psychiatric comorbidities in people with ADHD. Randomised controlled trials are needed to answer the question whether use of ADHD medication reduces the use of antipsychotic medication in people with intellectual disability and ADHD. Further studies are also needed to explore reason for not using ADHD medication in certain patients with ADHD and intellectual disability and what treatment options are effective in treating psychiatric comorbidities in people with ADHD and intellectual disability.